PERHITUNGAN WETON PRA PERKAWINAN ADAT JAWA MENURUT PERSEPSI MASYARAKAT PERSPEKTIF MASLAHAH MURSALAH (Studi Kasus di Desa Banjaragung Kecamatan Bareng Kabupaten Jombang) - Liza Novia Anggraini; Masrokhin Masrokhin (JOURNAL SAINS STUDENT RESEARCH, 2024)
This thesis is the result of the author's research and thoughts entitled "Community Perceptions Regarding Weton Calculation in Javanese Traditional Pre-Wedding Traditions According to Maslahah Mursalah Perspective (Case Study in Banjaragung Village, Bareng District, Jombang Regency)". This research aims to answer the questions stated in the problem formulation, namely what is the perception of the people of Banjaragung Village regarding the tradition of calculating weton to determine prospective bridal couples. What is the maslahah murrasa's perspective on the calculation of Javanese traditional wedding weton in Banjaragung Village.The type of research the author uses is qualitative, applying a qualitative descriptive approach. The data collection methods used are interviews, observation, documentation. And the data is analyzed by reducing the data, explaining the data, and drawing conclusions.The results of this research show that some people in Banjaragung Village still carry out weton calculations when carrying out marriages and have the ability to carry out weton calculations, by calculating the Javanese calendar as a reference used to determine whether a marriage is good or bad. From a maslahah perspective, the weton calculation does not conflict with religion, as long as its practice does not cause people to fall in trust in existing religious regulations. Because the aim of these traditional traditions is to maintain the benefit and protect the goals of maqasid syar'i, as well as a form of prudence in living life.